Fluvial response to Late Pleistocene and Holocene environmental change in a Thames chalkland headwater: the Lambourn of southern England. Issue 6 (December 2015) - Newell, Andrew J.; Sorensen, James P.R.; Chambers, Jonathan E.; Wilkinson, Paul B.; Uhlemann, Sebastian; Roberts, Colin; Gooddy, Daren C.; Vane, Christopher H.; Binley, Andrew
Abstract: This paper describes the Late Pleistocene to Holocene stratigraphy of the River Lambourn; a minor headwater of the River Thames in the Berkshire Downs. The Quaternary valley-fill comprises around 5–8 m of Late Pleistocene gravels overlain by Holocene peats and chalky clays. Quaternary deposits overlie an irregular rockhead erosion surface with deep scouring particularly evident on prominent bends in the valley. The gravels subdivide into a lower unit of chalky gravels overlain by coarse flint gravels. Ground penetrating radar suggests that gravels at depth are relatively structureless, but at the top show well-developed point-bar accretion surfaces which occur in association with peat-filled sinuous channels. These probably date from around the Pleistocene-Holocene boundary and may have formed in response to climate change and increased groundwater outflow as stream hydrology changed from the short-duration, high-magnitude flows of the Lower Dryas to the uniform, low-magnitude flows of the Holocene. Holocene peats initially infilled abandoned floodplain channels at around 10 kyr BP but later encroached over much of the Lambourn floodplain. A progressive upward decrease in organic material and an increase in the proportion of chalky clays from around 4 kyr BP probably occurred in response to floodplain accretion coupled with increased erosion of the chalk catchment related to agricultural clearance and a wetter climate.